Cyberbullying: a dignidade da pessoa humana e as relações educacionais - Fidalgo, Adriano Augusto (2024)
The theme of the thesis is: “Cyberbullying: the dignity of the human person in educational relationships”. The main challenges generated by cyberbullying in the educational field will be explained, notably taking into account the angles of observation and perception of teachers and managers, with respect for the dignity of the human person as a central point. With the acceleration of the use of remote classes and other technological communication tools, enhanced by the pandemic, conflicts that already existed in person also occur through communication and information applications and systems. Thus, cyberbullying is a concern, as it can have repercussions on the mental health of those involved, in the decline of school performance, in learning difficulties, in issues of school dropout and, in the most serious cases, in the occurrence of violence against victims and in situations of self-harm and suicide. These situations require confrontation with public policies, seeking to prevent and combat cyberbullying, as well as with the verification of successful cases in educational institutions. In view of the above, the occurrence of cyberbullying, which may be practiced on communication networks linked to school environments and the types of damage that result from it and that reach daily life, is the main issue of this thesis, since it can occur between students and teachers, students and other members of the school community and among colleagues. The general objective of the thesis is to assess educators' perception of violent behavior characterized as cyberbullying and which is configured in hate speech, cancellations, digital and in-person crimes and violation of basic human rights, notably in the educational field, with the subsequent verification of the constitutional principles that communicate with the dignity of the human person. And as specific objectives: a) to identify the experiences of teachers and managers in the occurrences; b) to survey court decisions that addressed the issue of cyberbullying and to analyze whether the existing legislation is sufficient to minimize occurrences; c) to list the main human rights violated and how they were resolved in schools. Theoretically, the concepts and definitions of cyberbullying will be addressed, as well as a literature review and applicable legislation. Regarding human dignity, it will be discussed in its interconnection with human development, human rights, fundamental rights, digital human rights and the weaknesses of the cancel culture, overexposure and digital risks. Education will be analyzed in the light of Edgar Morin's complex thinking, the use of information and communication technologies, the Law of Guidelines and Bases (LDB), the National Common Curricular Base (BNCC), digital education, cybercitizenship and a culture of peace. Interviews with teachers and school administrators were conducted and analyzed, confirming our hypotheses, that is, the need for educational institutions to deepen their focus on human rights education, in order to protect the human dignity of young people against systematic intimidation. In conclusion, the critical use of technology is necessary, with the development of cybercitizenship that respects human dignity in the educational environment, with the implementation of protocols to combat and prevent cyberbullying.